2007
DOI: 10.1117/1.2564793
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of adenocarcinoma and squamous cell carcinoma of the gastroesophageal junction

Abstract: Photodynamic therapy (PDT) is an alternative to radical surgical resection for T1a or nonresectable carcinomas of the gastroesophageal junction. Besides the concentration of the photosensitizer, the light distribution in tissue is responsible for tumor destruction. For this reason, knowledge about the behavior of light in healthy and dysplastic tissue is of great interest for careful irradiation scheduling. The aim of this study is to determine the optical parameters (OP) of healthy and carcinomatous tissue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 26 publications
3
55
3
Order By: Relevance
“…The reason for the difference of the oxy-hemoglobin peak found in this study but not found by Holmer et al [8] can be partly caused by the lower wavelength resolution Holmer et al [8] used (10 nm). Moreover, it should also be noted that Holmer et al [8] measured human esophagus and in this study pig esophagus is used. A further indication that the usage of pig esophagus might lead to different measured absorption coefficient can be found by comparing the results of this study with the newer results of Jones et al [7] where they measured the optical properties of pig esophagus.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…The reason for the difference of the oxy-hemoglobin peak found in this study but not found by Holmer et al [8] can be partly caused by the lower wavelength resolution Holmer et al [8] used (10 nm). Moreover, it should also be noted that Holmer et al [8] measured human esophagus and in this study pig esophagus is used. A further indication that the usage of pig esophagus might lead to different measured absorption coefficient can be found by comparing the results of this study with the newer results of Jones et al [7] where they measured the optical properties of pig esophagus.…”
Section: Discussioncontrasting
confidence: 78%
“…They also measured a higher absorption coefficient in the blue region and the region of the blood peaks. This difference is caused by the storage time of the sample in this study while Holmer et al [8] used fresh puré ed samples, the samples in this study had to be stored for few hours before they could be measured. The reason for the difference of the oxy-hemoglobin peak found in this study but not found by Holmer et al [8] can be partly caused by the lower wavelength resolution Holmer et al [8] used (10 nm).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations